Hierarchically pure and M (Cu, Ni)-impregnated ZSM-5 zeolites for the isomerization catalysis of n-hexane and 1-hexene. (15th November 2019) - Jesudoss, S K; Judith Vijaya, J; Iyyappa Rajan, P; John Kennedy, L; Mkandawire, Martin
Abstract: Conversion of bio-waste into high value catalytic materials is an option in the quest of maintaining sustainable environment. Here, we report an elaborated analysis of the catalytic activity of synthesized hierarchical pure and M (Cu, Ni)-impregnated ZSM-5 zeolite structures from the rice hull ash (RHuA), which is an abundant bio-waste material in most rice producing regions. To achieve the desired characteristics of ZSM-5 framework for metal (i.e., Cu and Ni) impregnation, an organic template-free method synthesis was designed. Further, the catalytic performance of the metal impregnated ZSM-5 in the isomerization of n-hexane and 1-hexene were carried out in a continuous flow stainless steel fixed bed reactor. Three (3) metal impregnation percentages, namely 1, 3 and 5% of Cu/Ni were investigated and compared in respect to the metals. The isomerization of higher alkanes/alkenes is crucial in petroleum industries to increase the octane number of gasoline. Reaction parameters of interest were catalyst amount, reaction temperature, weight hourly space velocity (WHSV), and reaction time were optimized and the obtained results are elaborately discussed. The Ni-ZSM-5 have superior catalytic activity compared Cu-ZSM-5, although the catalytic activity of ZSM-5 zeolite increases with the loading percentage for both Cu and Ni. To explain the metal loading effects on catalytic activity of the ZSM-5, density functional theory calculations were done through adsorption-desorption mechanistic approach. This combined experimental and theoretical investigation strongly validated the reliability of the results.